Work Performance Assessed by a Newly Developed Japanese Version of the Work Limitation Questionnaire in a General Japanese Adult Population. Issue 2 (3rd October 2014) - Takegami, Misa; Yamazaki, Shin; Greenhill, Annabel; Chang, Hong; Fukuhara, Shunichi
Abstract : Work Performance Assessed by a Newly Developed Japanese Version of the Work Limitation Questionnaire in a General Japanese Adult Population: Misa TAKEGAMI, et al . Department of Preventive Medicine and Epidemiologic Informatics, National Cerebral and Cardiovascular Center— Background: The Work Limitations Questionnaire (WLQ) was recently developed to measure health‐related decrements in ability to perform job roles among employed individuals. The purpose of this study was to develop and test a Japanese version of the WLQ. Methods: Developing the Japanese version of the WLQ involved translations, back‐translations, and a pilot study. Using data obtained from a nationwide survey, 4, 600 people aged ≥20 years were selected from the entire population of Japan by stratified random sampling. We ultimately used data from a total of 1, 358 workers out of 2, 266 subjects who filled out the self‐administered questionnaire. We computed the proportion of missing data, measured internal consistency reliability, and tested for convergent and discriminant validity, concurrent validity, known groups validity, and the factor structure of this instrument. Results: For the Japanese version of the WLQ, the percentages of missing values for each scale ranged from 3.6% to 7.8%. Internal consistency reliability was high, and Cronbach's α was ≥0.7 for all subscales. Subjects with headache and orthopedic pain had significantly higher WLQ subscale scores than subjects without. Higher WLQ subscale scores were associated with depressive symptoms as measured with the Hospital Anxiety and Depression Scale ( p <0.001). Conclusions: The Japanese WLQ provides reliable and valid information on at‐work disability for group‐level comparisons and tracking therapeutic outcomes.